Cytotoxic Activities of Bioactive Fraction of Uncaria gambir (Hunter) Roxb on MCF-7 Human Breast Cancer Cell Line - Nanang Yunarto; Humaira Fadhilah; Rini Purnamasari; Uud Nourma Reswandaru (Jurnal Kefarmasian Indonesia, 2025)
Breast cancer is a disease with the highest mortality rate. The first line of breast cancer treatment uses chemotherapy, but it has serious side effects on patients. Gambir (Uncaria gambir (Hunter) Roxb.) contains catechin compounds that show cytotoxic activity. This study aims to evaluate the antioxidant activity and cytotoxic effects on MCF-7 human breast cancer cells from the bioactive fraction of gambir leaves. Gambir extract was fractionated with water, ethyl acetate, and n-hexane solvents. Determination of catechin levels in the fractions used high-performance thin-layer chromatography. Antioxidant activity was tested using 2,2'-diphenyl-1-picrylhydrazyl (DPPH) and cytotoxicity tests on MCF-7 cells were carried out using MTT assay with inhibition of protein expression anti-apoptosis was determined by immunocytochemistry assay. The ethyl acetate fraction had the highest catechin content, namely 93.05%. The results of the antioxidant activity test showed that the IC50 values were consecutively for the water fraction 42.48 µg/mL, ethyl acetate 14.86 µg/mL, and n-hexane 49.63 µg/mL. In the MTT test, the ethyl acetate fraction had more potent cytotoxic activity with an IC50 value of 87.52 µg/mL. This study shows that the ethyl acetate fraction of gambir leaves has potent antioxidant and cytotoxic activity. The higher catechin content relates to antioxidant and cytotoxic activity against MCF-7 cells.